Anticardiolipin antibodies: occurrence in Behçet's syndrome. Issue 5 (October 1984) - Hull, R G; Harris, E N; Gharavi, A E; Tincani, A; Asherson, R A; Valesini, G; Denman, A M; Froude, G; Hughes, G R
Abstract : Anticardiolipin antibodies have recently been described in association with arterial and venous thrombosis, and with neurological symptoms, in connective tissue diseases. In a study of 70 patients with Behçet's syndrome 13 patients had these antibodies. Of these 13 patients eight had a history of either retinal vascular pathology, cerebral infarction, or thrombophlebitis. The association of retinal vascular disease and the presence of anticardiolipin antibodies was statistically significant.